(untitled) (Sound Stage Screen, 2024)
Recently, the use of Geographic Information System (GIS) in the field of urban music studies has been increasing. The article will address the benefits and risks ingrained in its employment and highlight the importance of adopting a blended approach such as the one proposed by “deep mapping.” Over the past decade, the constellation of mapping practices associated with the “depth” metaphor has shown the potential of GIS as an experiential platform, capable of including both quantitative data and qualitative multimedia content. Next, I will present the advantages of using Leaflet for R, an open-source web-mapping library, in the creation of deep maps. Its accessibility, even for non-professional programmers, makes it a valid alternative to commercial platforms. In the second part of this article, I will showcase my research on Milan’s live music scene from 1958 to 1962 as a case study. I will illustrate how the flexibility of these tools allowed me to develop a circular workflow that integrates historical sources, field research, and data visualization.